The Wind Farm Simulator of Reflected Signals in Primary Radar System - Pidanič, Jan; Juryca, Karel; Suhartanto, Heru (University of Indonesia, 2017)
The spreading of the renewable energy especially wind farms, increases possibilities of negative influence on the detection capabilities of primary radar systems. The paper deals with modelling of a simulator for reflected signals from wind farms. The developed simulator enables echo simulation from wind farms, with many variable input parameters, that helps with analysis of influence. The simulator simplifies and speeds up the development of wind farm mitigation techniques, on primary radar systems. The paper describes characterization of the model of the simulator that includes multipath reflection and a brief analysis
Simulátor odražených signálů od větrných elektráren pro primární radarové signály
Keywords: wind turbine; power plant; primary radar system; clutter; reflection, Radar Cross Section, wind farm, Doppler shift; větrná elektrárna; elektrárna; primární radarový systém; clutter; odrazy signálů; efektivní odrazná plocha; Dopplerovský posun